EKSPLORASI ALAT MUSIK SUKU KARO GUNG DAN PENGANAK TERHADAP KONSEP LINGKARAN - Silangit, Menna Sri Ulina; Tambunan, Hardi; Simanjuntak, Ruth Mayasari (Universitas Quality, 2024)
Mathematics learning that uses the circle concept using contextual concepts can make it easier for students to understand mathematical concepts and also broaden students' insight. This research aims to explore the shapes and patterns of Karo musical instruments, namely the gung and Penganak, which will then be used as material for developing learning resources based on the cultural diversity that exists in Tanah Karo. The method used in this research is exploratory with an ethnographic approach. The instrument used in this research is a human instrument, and the data collection techniques used by researchers are observation and documentation. From this research it was found that gung and penganak are flat, circular shapes which can be related to mathematics learning.